Pyogenic Granuloma like Kaposi Sarcoma: A Diagnosis Easily Missed - George, Smiley Annie; Francis, Issam Michel (Annals of Pathology and Laboratory Medicine, 2021)
Pyogenic granuloma-like Kaposi sarcoma (PG-like KS) is a clinicopathologic variant of Kaposi sarcoma (KS), a vascular tumor caused by human herpesvirus-8 (HHV-8). PG-like KS is a challenging entity to diagnose because its clinical and histological features encompass features of both pyogenic granuloma (PG) and KS Distinction between the two entities is clinically important as the management is different. KS patients requires evaluation of their immunodeficiency status and follow-up. Throwing a HHV-8 LNA-1 immunohistochemistry helps in clinching the diagnosis. Recognition of the precise histological features and clinical correlation can facilitate the correct diagnosis.